Network pharmacology, molecular docking, and molecular dynamics analyses to explore the molecular mechanism of paclitaxel in atherosclerosis therapy - Oktomalioputri, Biomechy; Afriwardi, Afriwardi; Darwin, Eryati; Rita, Rauza S. (Narra Sains Indonesia, 2025)
Atherosclerosis is a chronic arterial disease and the leading cause of vascular death. Paclitaxel has long been recognized as an anticancer agent, but recent studies have shown that paclitaxel can also potentially reduce the progression of atherosclerosis. The aim of this study was to explore the molecular mechanism of paclitaxel as an atherosclerosis therapy using in silico study. Pharmacokinetic and pharmacodynamic analyses of paclitaxel were conducted using SwissADME, ProTox v3.0, and SCFbio websites. Cytoscape software was used to construct a network of protein-protein interactions, and the key proteins involved in paclitaxel-related atherosclerosis were identified, including AKT serine/threonine kinase 1 (AKT1), Jun N-terminal kinase (JNK), and Endothelin 1 (ET1). These key proteins were then subjected to molecular docking and molecular dynamic simulation using MOE and Yasara applications. Pharmacokinetic and pharmacodynamic analyses revealed that paclitaxel has good distribution, metabolism, and excretion properties. However, paclitaxel has shortcomings in absorption, toxicity, and water solubility. According to the results of molecular docking, paclitaxel showed consistent results as the most potential inhibitor of AKT1 (-9.59 kcal/mol), ET1 (-9.16 kcal/mol), JNK (-8.72 kcal/mol) when compared to the control ligands. Molecular dynamics simulations also confirmed the interaction stability between paclitaxel with AKT1, ET1, and JNK, with paclitaxel-AKT1 demonstrating the highest conformational stability (Carbon-α Root Mean Square Deviation <3.0 Å). Even though our in-silico results are promising, more experimental studies are required to confirm the efficacy of paclitaxel as an atherosclerosis therapy.